An Ionophore‐Based Anion‐Selective Optode Printed on Cellulose Paper. Issue 39 (16th August 2017) - Wang, Xuewei; Zhang, Qi; Nam, Changwoo; Hickner, Michael; Mahoney, Mollie; Meyerhoff, Mark E.
Abstract: A general anion‐sensing platform is reported based on a portable and cost‐effective ion‐selective optode and a smartphone detector equipped with a color analysis app. In contrast to traditional anion‐selective optodes using a hydrophobic polymer and/or plasticizer to dissolve hydrophobic sensing elements, the new optode relies on hydrophilic cellulose paper. The anion ionophore and a lipophilic pH indicator are inkjet‐printed and adsorbed on paper and form a "dry" hydrophobic sensing layer. Porous cellulose sheets also allow the sensing site to be modified with dried buffer that prevents any sample pH dependence of the observed color change. A highly selective fluoride optode using an Al III ‐porphyrin ionophore is examined as an initial example of this new anion sensing platform for measurements of fluoride levels in drinking water samples. Apart from Lewis acid–base recognition, hydrogen bonding recognition is also compatible with this sensing platform. Abstract : Cellulose paper as a sole substrate allows adsorption of a lipophilic anion ionophore and pH‐sensitive indicator dye to enable heterogeneous anion sensing via an anion‐proton co‐extraction mechanism. This platform also enables adsorption of a buffer salt as the sample pH adjuster to prevent pH dependence of the optical anion response.